Pengelompokan Merek Susu Ultra High Tempherature Berdasarkan Kemiripan Kandungan Gizi Menggunakan Analisis Biplot - Swithania Rizka Putri; Nonong Amalita (UNIVERSITAS NEGERI PADANG, 2020)
Abstract— Milk have benefits as a type of healthy food. The nutritional content of milk has many benefits for the body. Ultra High Temperature Milk is one type of processed milk that has large demand by public. In order for people to choose the type of Ultra High Temperature milk based on the nutritional content they need. This study aims to determine the milk brand groups that have similar nutritional content and diversity of the nutritional content. Data that used in this research is secondary data which gathered from UHT milk’s producer from any website. Biplot analysis can be used to get the information of which group of UHT milk’s brand that has the same nutritional content. The result from Biplot Analysis showed that total fat content had a great diversity than the others in all milk brands, and there were 12 groups of milk brands that had similar nutritional content. Keywords— Nutritional Content, Ultra High Tempherature, Biplot Analysis